Complete genome sequence of yellow pigment-producing sphingobium sp. strain HAL-16 - Kwon, Soon Jae; Lee, Pyung Cheon (Microbiology Resource Announcements, 2020)
Sphingobium sp. strain HAL-16, which was isolated from Antarctic soil samples, synthesizes a yellow pigment. The complete genome consists of a single circular chromosome (4,372,398 bp, with a G+C content of 62.7%) and a single circular plasmid (57,025 bp, with a G+C content of 59.4%). Five genes encoding carotenogenic enzymes were identified, suggesting that the yellow pigment is a hydroxy/keto- β-carotene.